Ekspresi-dasar arsitektural pada bangunan pusat kebudayaan, objek studi: Volkstheater Sobokartti di Semarang, Indonesia - Nabila Sukada; Purnama Salura (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Basic architectural expression of a cultural center, study object: Volkstheater Sobokartti in Semarang, Indonesia The absence of specific guidelines is the main reason that cultural centers in Indonesia were often using an existing building that is not designated as cultural center and/or are designed with modern styles that are completely different from the existing architectural styles. This research is specifically focused on the issue of basic architectural expression in the Volkstheater Sobokartti Cultural Center. The main purpose of this research is to reveal architectural meaning based on the basic-expression of the Volkstheater Sobokartti Cultural Center. This research utilized theories such as: cultural center, architectural expression, and interpretation of architectural meaning. These theories together with the study object are then analyzed and elaborated in-depth using architectural anatomy and ordering principles theories. This research succeeded in compiling a reference of basic architectural expression as a basis for designing and/or interpreting the meaning of a cultural center. The result of this research can be used as: a design input/consideration for architects and stakeholders in designing and/or interpreting the meaning of a cultural center for students, academicians, architects, and concerned community; a starting point for other similar research.